Black Adam [videorecording (DVD)] - Sztykiel, Adam; Haines, Rory, 1984-; Noshirvani, Sohrab; Johnson, Dwayne, 1972-; Hodge, Aldis; Centineo, Noah, 1996-; Shahi, Sarah, 1980-; Kenzari, Marwan, 1983-; Swindell, Quintessa, 1997-; Sabongui, Bodhi; Amer, Mohammed; Cusati-Moyer, James; et al. (Warner Bros. Entertainment Inc., 2023)
Nearly 5,000 years after he was bestowed with the almighty powers of the Egyptian gods-and imprisoned just as quickly-Black Adam is freed from his earthly tomb, ready to unleash his unique form of justice on the modern world.